1983
DOI: 10.1095/biolreprod28.2.385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Histamine and Histamine Blockers on the Ovulatory Process in the in Vitro Perfused Rabbit Ovary

Abstract: An increase in the content of histamine in the ovary following luteinizing hormone (LH) release and the inhibition of ovulation in the rabbit by antihistamines suggest that histamine may be involved in the ovulatory process. The effects of various doses of histamine and antihistamines on ovulation were investigated using the in vitro perfused rabbit ovary system. Histamine (100 ng/ml) added to the perfusate at hourly intervals induced ovulation, although at a rate below that observed following human chorionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…This agrees with the incidence found by Kobayashi et al (1983), who also reported that follicle growth and rupture differed in rabbit ovaries exposed to histamine or LH: a characteristic apex or stigma was not present, and the oocytes often remained in an immature stage. Moreover, the action of histamine in the present study did not require an intact prostaglandin synthesis system, whereas indomethacin blocks the gonadotrophin-stimulated follicular rupture (Armstrong, 1981).…”
Section: Effect Of An H\-antagonistsupporting
confidence: 91%
See 3 more Smart Citations
“…This agrees with the incidence found by Kobayashi et al (1983), who also reported that follicle growth and rupture differed in rabbit ovaries exposed to histamine or LH: a characteristic apex or stigma was not present, and the oocytes often remained in an immature stage. Moreover, the action of histamine in the present study did not require an intact prostaglandin synthesis system, whereas indomethacin blocks the gonadotrophin-stimulated follicular rupture (Armstrong, 1981).…”
Section: Effect Of An H\-antagonistsupporting
confidence: 91%
“…However, this antagonist, like chlorpheniramine, lowered the number of ovulations induced with histamine in the isolated perfused rabbit ovary (Kobayashi et al, 1983). The present experiments on rat ovaries agree with reports from studies on rabbits suggesting that the histamine-induced ovulation involves both receptor subtypes (Wallach et al, 1978;Kobayashi et al, 1983).…”
Section: Effect Of An H\-antagonistmentioning
confidence: 98%
See 2 more Smart Citations
“…Histamine is involved in the various stages of reproduction including ovulation [Szego and Gitin 1964;Schmidt et al 1988;Kobayashi et al 1983;Jaiswal and Krishna 1994;Schmidt et al 1987;Halterman and Murdoch 1986;Kitai et al 1985], implantation [Liu et al 2004;Zhao et al 2000;Paria et al 1998;2002;Oikawa et al 2003;Hoos and Hoffman 1983], and decidualization [Shelesnyak 1960;Zipper et al 1965]. Various researchers have demonstrated that H 2 receptor blockers possess anti-fertility activity [Agrawal and Alvin Jose 2009;Agrawal and Aravinda 1995;Brandon and Wallis 1977].…”
Section: Introductionmentioning
confidence: 99%